Influence of hypertension, left ventricular hypertrophy, and left ventricular systolic dysfunction on plasma N terminal proBNP. Issue 3 (1st March 2000) - Talwar, S; Siebenhofer, A; Williams, B; Ng, L
Abstract : OBJECTIVES: To examine the relation between plasma concentration of the N terminal of the precursor of brain natriuretic peptide (NT proBNP), left ventricular hypertrophy (LVH), and left ventricular systolic dysfunction (LVSD) in patients with a history of hypertension. DESIGN: Prospective study. SETTING: Teaching hospital based study. PATIENTS: NT proBNP concentrations were determined in five groups of individuals. Group 1: 15 echocardiographic normal controls; group 2: 22 patients with hypertension, normal left ventricular systolic function, and no LVH; group 3: 24 patients with hypertension, normal left ventricular systolic function, and LVH; group 4: 13 patients with history of hypertension, no history of ischaemic heart disease, and left ventricular wall motion index (WMI) between 1.9–1.3; and group 5:17 patients with a history of hypertension, no history of ischaemic heart disease, and WMI < 1.2. RESULTS: Median (range) NT proBNP concentrations (in fmol/ml) for groups 1–5, respectively, were: 129.4 (53.6–159.7), 147.4 (54.3–730.5), 137.1 (35.8–403.9), 356.7 (124.4–934.4), and 493.5 (248.9–909). Mean log NT proBNP differed among all five groups (p < 0.0001), and between groups 4 and 5 versus groups 1–3 (p < 0.0001), and group 4 versus group 5 (p = 0.02) only. CONCLUSIONS: The results suggest that the presence of hypertension with or without LVH (and normal left ventricular systolic function) does not affect NT proBNP concentrations. Moreover, there is a significant rise in NT proBNP only when LVSD develops in hypertension. Thus, NT proBNP remains a useful diagnostic aid for LVSD, even in hypertensive patients.